6(2x-9)=2(6x+1)

Simple and best practice solution for 6(2x-9)=2(6x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-9)=2(6x+1) equation:


Simplifying
6(2x + -9) = 2(6x + 1)

Reorder the terms:
6(-9 + 2x) = 2(6x + 1)
(-9 * 6 + 2x * 6) = 2(6x + 1)
(-54 + 12x) = 2(6x + 1)

Reorder the terms:
-54 + 12x = 2(1 + 6x)
-54 + 12x = (1 * 2 + 6x * 2)
-54 + 12x = (2 + 12x)

Add '-12x' to each side of the equation.
-54 + 12x + -12x = 2 + 12x + -12x

Combine like terms: 12x + -12x = 0
-54 + 0 = 2 + 12x + -12x
-54 = 2 + 12x + -12x

Combine like terms: 12x + -12x = 0
-54 = 2 + 0
-54 = 2

Solving
-54 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 10x+2+4x+8=13x+3 | | 2.34+0.23h=6.25 | | 9+18r-8=6r+145-4r | | -3+(-1/6)= | | 3/750=x/10000 | | 11x-[3x+(-1+3x)]=0 | | p^2+11p=0 | | 3b-4-8b-6= | | 8(3x-4)=16 | | 12+30x=64 | | 7x^2+19x-16=0 | | 4x=2.5 | | 8n+9n=68 | | 7+1/9= | | 3/7(4/3)= | | -0.6+0.05h=5.3 | | 5x^2+41x-36=0 | | -30=3n-12 | | -8+8n+3n=-7+11n | | 0=-16t^2+vt-36 | | 7x+56-42=x+53 | | 8(-1+7k)=6(6k+2) | | 4m-6m=6(m-5)+5(4-2m) | | 6(-8)-4(-9)=19 | | 4.28-0.4h=1.48 | | 2(3x-5)-8=-48 | | 12x+7= | | 2p+3-3p+9=10 | | 15x^2+7x+2=0 | | 3.1q-4.6-2.5q=0.4q-4.8 | | 2x+8-4x=-2(x-4) | | 6d-57=7 |

Equations solver categories